The Use Of Fractal Theory In Digital Signal Processing In Radio Communication Systems - Davronbekov Dilmurod Abdujalilovich; Tuychiev Bekzod Oromovich (The American Journal of Engineering and Technology, 2020)
When digital signal processing in a radio communication system, it is advisable to calculate the fractal dimension D and the Hausdorff dimension based on the topological mathematical expression D_0, analyze the methods of digital signal processing by the electro-optical method, i.e. perform experimental calculations of fractal points.